Isolation and Molecular Identification of Novel Chicken Feather Degrading Bacteria Bacillus tropicus KRKJVR 5 - Kumar, K. Raja; Nikhitha, Lakavath.; Venkanna, Soorarapu.; Rao, J. Venkateshwara (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The isolation and molecular identification of a novel chicken feather-degrading bacterium, Bacillus tropicus KRKJVR 5, were conducted to explore its potential in biotechnological applications. Soil samples collected from various sites in Suryapet district, Telangana, were screened using the enrichment culture method to identify potential keratinolytic producers. A total of ten bacterial isolates were initially identified, out of which five isolates demonstrated significant feather degradation on feather-containing agar media. Among these, Isolate 5 exhibited the highest keratinase activity, completely degrading feathers within 48 hours and producing 8.66 U/ml of keratinase, as determined by the Azocasein assay. Morphological and biochemical tests characterized Isolate 5 as a rod-shaped, Gram-positive Bacillus species with positive results for spore staining, Voges-Proskauer, catalase, starch hydrolysis, and carbohydrate fermentation tests, and negative results for indole, methyl red, citrate, H2S, and urease tests. Definitive genetic identification through 16S rRNA sequencing and comparison with the NCBI database confirmed Isolate 5 as Bacillus tropicus KRKJVR 5, with a 92% similarity to other Bacillus tropicus strains. The sequence data was submitted to NCBI and assigned the accession number PP859287. These findings highlight the potential of Bacillus tropicus KRKJVR 5 for efficient keratin degradation, making it a promising candidate for various industrial and environmental applications.